Physical and mechanical characterization of electrodeposited nickel nanowires - influence of current density and external magnetic field - Mahendran, Samykano (2015)
Magnetic 1-D nano structures have received great interest due to their various applications including high-density magnetic storage, sensors, drug delivery, and NEMS/MEMS systems. Among different 1 -D nanostructures, magnetic nickel (Ni) nanowires with their ferromagnetic properties are of interest in such applications due to their lower cost, and they can be consistently synthesized via electrodeposition. While physical properties are influenced by processing parameters during electrodeposition of Ni nanowires, understanding of their influence on the mechanical properties is still not available. This is primarily due to the following challenges: tediousness involved in experimental techniques for mechanical characterization at nanoscale; sophisticated and careful experimentation required to be performed with advanced microscopy systems (SEM, AFM); robust nanoscale manipulators needed to place a single nanowire within the device; and difficulty in correctly loading and obtaining data for stress-strain within high powered microscopy environments. All of these factors pose significant challenges, limiting the current state of the art in mechanical characterization to its infancy, with wide differences in characterization curves and reported properties in this field. The present research and dissertation focuses on: 1. Experimental synthesis of electrodeposited Ni nanowires at different current densities and external magnetic fields, 2. Physical properties characterization of the synthesized nanowires to understand their morphology, structural and crystallographic properties, 3. Mechanical properties characterization of synthesized Ni nanowires through careful experiments within scanning electron microscope (SEM) based on uni-axial MEMS tensile loading device, 4. Data analysis to understand the process, physical and mechanical property interrelationship and to obtain insights on tensile deformation and failure modes observed in the Ni nanowires studied. Key research insights from the present experimental research include: Electrodeposition method consistently synthesizes high purity Ni nanowires (98% and higher based on energy dispersive spectroscopy (EDS)) with a significant improvement in surface morphology when magnetic field is present during synthesis; X-ray diffraction (XRD) characterization and analysis indicate that electric current density has significant influence on the crystal orientation of Ni nanowire, while a decrease in crystal size was noticed with increased magnetic field intensity for same current densities. Carefully studied uni-axial tensile characterization using MEMS tensile loading device indicates an increase in elastic tensile modulus when the magnetic field is present during electrodeposition and consistent observation of three different variants of ductile failure modes. Results and discussions of tensile stress-strain mechanical characteristics ofNi rianowires and their failure modes provide key research findings that are not currently available in the literature to our knowledge. The present research contributes to the experimental understanding of tensile deformation of Ni nanowires, as well as developing and presenting a robust experimental methodology for future extension to other metallic nanowires. Research findings clearly illustrate a need for three-dimensional high fidelity experimental tools and relevant computational modeling for a full understanding and insight on deformation and failure mechanisms involved at nanoscale.